Efek Dominasi Peran Gender Terhadap Keberlanjutan Pola Nafkah Usaha Budidaya Murbei dan Pemeliharaan Ulat Sutera - Adam, Andi Maslia Tenrisau (Journal Galung Tropika, 2020)
Mulberry cultivation and silkworm maintenance are household agro-industries with short production processes, which can be done by men and women and produce quickly. The research aims to analyze the role of gender in the household of mulberry cultivation and silkworm maintenance and analyze the effect of gender roles' dominance on the sustainable livelihood of the mulberry cultivation and silkworm maintenance. This research is a qualitative descriptive with case studies in nine businesses of mulberry cultivation and silkworm maintenance in Sabbangparu District, Wajo Regency. Research informants were purposive. Data were analyzed using a qualitative approach. The results showed that gender roles in roles allocation (reproductive, social, productive), economic allocation, and power allocation were dominated by wives (consecutively 51.94%, 47.08%, and 52.48%). High-income households, wives play a dominant role in allocating the positions while the power allocation tends to be decided together (husband and wife). The dominance of gender roles (husband and wife) in households does affect the sustainability of livelihood. Therefore, the husband and wife's involvement becomes necessary so that the mulberry cultivation and silkworm maintenance can run well and sustainably.